Correlation Between Glutathione Plasma with Degree Severity of Melasma in Balinese Women - Wiraguna AAGP; Hari ED; Praharsini IGAA (Dove Medical Press, 2020)
Anak Agung Gde Putra Wiraguna, Embun Dini Hari, I Gusti Ayu Agung Praharsini Dermatology and Venereology Department, Faculty of Medicine, Universitas Udayana-Sanglah General Hospital, Denpasar, Bali, IndonesiaCorrespondence: Anak Agung Gde Putra WiragunaDermatology and Venereology Department, Faculty of Medicine, Universitas Udayana-Sanglah General Hospital, Denpasar, Bali, IndonesiaEmail wiraguna@unud.ac.idIntroduction: Melasma is a condition of hyperpigmentation of the facial skin that increases in prevalence with ageing. The alleged involvement of reactive oxygen species and antioxidants is the basis of the pathology of melasma. Glutathione is one of the non-enzymatic antioxidants produced by the body and plays a role in melanogenesis. The purpose of this study was to examine serum glutathione levels on the severity of melasma.Methods: This study used a cross-sectional design conducted at the Cosmetic Dermatology Clinic at Sanglah Hospital, Denpasar, from September to October 2016. Serum glutathione was examined through venous blood with ELISA method, and the severity of melasma was assessed using melasma area severity index (MASI). Independent t-test and ANOVA were used to evaluate differences in plasma glutathione levels based on the characteristics of the sample. Pearson correlation test and linear regression were used to assess the relationship between MASI and plasma glutathione.Results: This study involved 47 people with a clinical diagnosis of melasma. There was a significant strong negative correlation between plasma glutathione and MASI (p< 0.001; r = − 0.624). Mild melasma (1.89 ± 0.28 μmol/L) had higher plasma glutathione levels compared to moderate melasma (1.53 ± 0.13 μmol/L) and severe (1.18 ± 0.20 μmol/L) (p=0.043). Linear regression showed a significant negative linear relationship between MASI scores against plasma glutathione (β = − 58.2; p < 0.01).Conclusion: Glutathione plasma has a strong negative correlation with the MASI score in person with melasma.Keywords: melasma, skin, pigmentation, glutathione